Johan Lansen 1933-2019 - Christian Pross (Torture)
Johan Lansen, a deeply-valued colleague, teacher, advisor, clinical supervisor and personal mentor for many, died at age 86 on November 26, 2019 in his hometown of Amersfoort in the Netherlands.